Magnetic activated biochar nanocomposites derived from wakame and its application in methylene blue adsorption - Yao, Xinxin; Ji, Lili; Guo, Jian; Ge, Shaoliang; Lu, Wencheng; Cai, Lu; Wang, Yaning; Song, Wendong; Zhang, Hailong (Bioresource technology, 2020)
[Display omitted] •The novel magnetic activated biochar nanocomposites were first time prepared using wakame.•Loading nickel on the surface of wakame biochar is conducive to its recycling.•The adsorption process is a spontaneous endothermic process.•At 293 K, the maximum adsorption capacity of MB is 479.49 mg/g. In this work, magnetic wakame biochar nanocomposites for the first time had been synthesized to investigate their adsorption to methylene blue dye. As-prepared magnetic biochar samples were obtained by the impregnation method to load nickel on wakame biochar via one-step carbonization with activation agent KOH at 800 °C. The prepared samples were characterized by BET, XRD, FTIR, Raman, SEM, TEM and so on. The results exhibited that the maximum adsorption capacity of BW(Ni)0.5 to methylene blue could reach 479.49 mg/g at 20 °C. The adsorption behavior was more suitable for Langmuir isotherm equation and the kinetic data were most consistent with the pseudo second-order model. And also, the adsorption reaction was a spontaneous and endothermic process. After five cycles, it was found that BW(Ni)0.5 had a high adsorption capacity for methylene blue (117.58 mg/g). This study demonstrated that wakame biochar could have great potential in dye wastewater treatment.